Evaluation and Management of Failed Hemiarthroplasty. Issue 20 (15th October 2018) - Sheth, Neil P.; Dattilo, Jonathan Ross; Schwarzkopf, Ran
Abstract : Hemiarthroplasty is a common procedure for treatment of displaced femoral neck fractures in low-demand patients. As hip fracture incidence continues to increase, the need for revision hemiarthroplasty is also expected to increase. Multiple etiologies can result in a failed hemiarthroplasty, including persistent pain, infection, instability, leg-length discrepancy, and trauma. Preoperative clinical, radiographic, and laboratory assessments are critical in determining the etiology of the painful hemiarthroplasty. The standard of care for surgical management of failed hemiarthroplasty is conversion to a total hip arthroplasty. However, establishing the etiology preoperatively is essential to planning before treating the failed hemiarthroplasty.